2010
DOI: 10.1103/physrevb.81.115451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface disorder on EXAFS modeling of metallic clusters

Abstract: Small ͑1-5 nm͒ metal clusters may undergo significant surface relaxation under the influence of ligands, adsorbates, and substrate-induced stress. As a result, the nearest-neighbor distance between surface atoms can be reduced by up to 10% relative to those in the cluster core, enhancing the disorder in the interatomic distances. Accordingly, the pair distribution function extracted from EXAFS data under the standard assumption that the distribution function of nearest-neighbor bonds is quasi-Gaussian yields s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 36 publications
4
118
0
Order By: Relevance
“…In this case, the interplay of theory and experiment provides a means to extract more accurate structural information from experimental EXAFS signals and to reduce the effects of tting artifacts that arise in disordered systems. 1,3 For example, one important limitation of EXAFS analysis is that it provides averaged information about the structure and dynamics of the nearest environment of all absorbing atoms in the nanoparticle ensemble, and this can lead to erroneous structural determinations if an "average" conguration is assumed to be the actual conguration. Specically, if the distribution of sizes, shapes, crystal structures, and states of order is broad, 4-6 then the notion of a "representative" nanoparticle is unhelpful at best, or, as recently shown, can lead to misinterpretation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the interplay of theory and experiment provides a means to extract more accurate structural information from experimental EXAFS signals and to reduce the effects of tting artifacts that arise in disordered systems. 1,3 For example, one important limitation of EXAFS analysis is that it provides averaged information about the structure and dynamics of the nearest environment of all absorbing atoms in the nanoparticle ensemble, and this can lead to erroneous structural determinations if an "average" conguration is assumed to be the actual conguration. Specically, if the distribution of sizes, shapes, crystal structures, and states of order is broad, 4-6 then the notion of a "representative" nanoparticle is unhelpful at best, or, as recently shown, can lead to misinterpretation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] One analytical method that is particularly amenable to combined theoretical and experimental studies is extended X-ray absorption ne structure (EXAFS) spectroscopy, and particularly its application to the analysis of small metallic nanoparticles. In this case, the interplay of theory and experiment provides a means to extract more accurate structural information from experimental EXAFS signals and to reduce the effects of tting artifacts that arise in disordered systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, a quantitative determination of this W metal fraction was prevented given the intrinsic difficulties of fitting EXAFS signals for amorphous systems, as mentioned above. 50,51 In spite of it, W L 3 EXAFS results show interesting trends as shown in Fig 10(a), where it is noticeable that the shoulder corresponding to the metallic W contribution increases as the amount of W increases in the sample (a series). A similar trend was also observed in their fitting results and is well in agreement to what was observed by HRTEM.…”
Section: B W L 3 Edgementioning
confidence: 98%
“…A reduction from N = 12 in the metallic Co to N = 6.1 in the first coordination shell of the bare Co nanoparticles was obtained from this fit. However, recent works have demonstrated that such a strong reduction in the number of first neighbors could be an artifact of EXAFS analysis, 50 due to effects of surface distortions on the nanoparticles, producing an underestimation of the average coordination number.…”
mentioning
confidence: 99%
See 1 more Smart Citation